Technical Report on Face to Face Training on “Introduction to e-learning courses in the framework of the SWC@scale project” - Rudiger, Udo (International Center for Agricultural Research in the Dry Areas, 2022)
Technical Report on Face to Face Training on “Introduction to e-learning courses in the framework of the SWC@scale project”.